Nódulo tireoidiano Bethesda III: cirurgia x observação - Bastos Filho, Luiz de Castro [UNIFESP] (2016)
Objectives: To determine the characteristics of the patients, both those who were operated as those followed clinically, considering the surgical criteria and correlate the puncture findings (especially in relation to the presence or absence of nuclear atypia in the sample) and sonographic findings with histopathological examinations. Methods: Eight hundred and three (803) patients underwent fine-needle aspiration (FNA) of thyroid nodules, totaling one thousand three hundred and seventy five (1375) punctures, in the years 2011, 2012 and 2013 in a thyroid disease treatment project in partnership between the UNIFESP / EPM and the Albert Einstein Hospital. Eighty-nine patients (11%) had at least one Bethesda III thyroid nodule. Only fifty-four (7%) met the inclusion criteria. Results: Of the fifty-four patients evaluated, 50 (92.5%) were female with a mean age 48.7 [19-83] years. Thirty-four (63%) patients had multinodular glands, four of them people with hyperthyroidism and twenty (37%) presented glands with single nodule. Twenty-five (46.3%) patients were operated after first FNA. Of these, fourteen (56%) were malign and eleven (44%) were benign. Twenty-nine (53.7%) patients were observed and repeted the FNA. Fourteen (48.3%) were operated showing malignancy in 6 (42.8%) and benign histopathological result in 8 (57.2%). Fifteen (48%) patients had benign report after the new FNA being referred for follow-up. Among the sonographic findings with low or very low suspicion, the majority (19) had benign histopathology report (45.2%). The quantitative reports with malignant results were higher in cases with nuclear atypia present, totaling 8 nodules (19.0%). However, associations were not identified between the results of histopathological reports and sonographic findings (p = 0.322) or the presence of nuclear atypia (p = 0.273; x² = 1.201, gl = 1). Conclusion: Data from this study show a higher incidence of malignancy in Bethesda III nodules than that described in the Bethesda System publication article and made clear the difficulty of maintaining following several patients and conclud that, although each one of these patients require careful analysis based on clinical, ultrasound and cytological findings, there should be more liberal in surgical indication and encouragement to follow-up by the medical team.